Կրոնական պակտերացումները որպես էթնիկական կարծրատիպերի ձևավորման աղբյուր և դրանց էթնոպաշտպան գործառույթը - Ղարախանյան, Լ.
One of indicators of greatest importance among the forms of ethnic self- identification is religious belonging /devotion/. Numerous protective functions of religious are reflected in the social-ethnic context, and influences the formation of ethnic stereotypes which presupposes certain behaviour manifested in appropriate conditions. The following article deals with the separate points of religious conceptions as a source of development of ethnic stereotypes and with their ethnoprotective function. С точки зрения этнической самоидентификации одим из наиболее значимых показателей является религиозная принадлежность. В социально-этническом контексте отражены многочисленные защитные функции религии, которая также влияет на формирование этнических стереотипов, что предполагает формирование определенного характера поведения в соответствующих условиях. В данной статье рассматриваются отдельные положения религиозных представлений как источники развития этнических стереотипов и их этно-защитные функции.
Keywords: Հոգեբանություն